Mg-doped TiO2 for dye-sensitive solar cell: An electronic structure study - Nam, Tran Van; Trang, Nguyen Thuy; Cong, Bach Thanh (VNU Journal of Science: Mathematics - Physics; Vol 28 No 2, 2012)
Abstract. Recently, there has been a renewed interest in TiO 2 anatase as charge transfer layer in dye-sensitized solar cells (DSSC). In this work, the electronic structure of Mg-doped TiO 2 anatase was explored in the framework of density functional theory (DFT). The results showed that the substitution of Mg 2+ ions for Ti 4+ ions was quite easy in comparison with non metalic doping case. It induced small lattice expansions about 0.3% along a and b axis and 0.1% along c axis which can be explained in terms of internal stress around the impurity site and the anisotropic softy of the material. The effects of Mg impurity on the bulk and surface electronic structures were also discussed in details. It caused a negative shift of the conduction band edge -1.16 eV and 1.142 eV for bulk and surface respectively. The Fermi level was also shifted 1 eV to the negative energy. Such effects were suggested to improve short-circuit current J SC of DSSCs but decrease the open-circuit voltage V OC .